(untitled) (Scientific journal of the Fergana State University, 2024)
Studiyes on ichthyofauna of ditches and collectors of Fergana oblast have been practically not carriyed out. This article describes currently occurring speciyes of ichthyofauna of ditches and collectors of Fergana region, their distribution areas, levels of occurrence and their status in the International Red Data Book. Eight fish speciyes were found in ditches of Fergana district. The most common speciyes with the highest number of individuals in the ditches of the district were Triplophysa strauchii and Schizothorax eurystomus, Triplophysa strauchii — 19.5% of the total number of speciyes, Schizothorax eurystomus — 16.0%, Petroleuciscus squaliusculus — 14.4%, Pseudorasbora parva - 13. ,3%, Triplophysa ferganaensis 10.8%, Carassius gibelio 9.0%, Abbottina rivularis was 7.76%. It was found that 6 speciyes were included in the International Red Data Book in the district ditches.